FREQUENCY OF HEPATITIS C INFECTION IN DIABETIC PATIENTS - Ali, Sobia S.; Ali, Irum Sabir; Aamir, A H; Jadoon, Zahid; Inayatullah, Saima (Journal of Ayub Medical College Abbottabad, 2007)
Background: Diabetic patients are at an increased risk of acquiring Hepatitis C virus (HCV) infection owing to the nature of the disease and its inherent complications or frequent parentral exposure. On the other hand HCV infection may itself contribute to the development of Diabetes Mellitus. The epidemiological evidence of this association has not been studied in Pakistan at a population level and its exact biological mechanisms are not obvious. Objective of this study was to study the frequency of HCV infection among adult diabetic patients attending the Hospital. Methods : The study comprised of 100 Diabetic patients visiting the out patient clinics or admitted in the medical wards of a Teaching Hospital, in Peshawar. Diabetes was confirmed according to the new diagnostic criteria based on 2 fasting or 2 random plasma glucose levels of more than 126 milligram per deciliter (mg/dL) and 200 mg/dL respectively. The presence of HCV infection was confirmed by Enzyme Linked Immuno-Sorbent Assay (ELISA) method. A concise history of the patient, examination and laboratory findings were recorded on a Performa. Results: Out of the hundred diabetics, 36% were found to be anti HCV positive and all of them had type II diabetes. There was no gender difference in the seropositive cases. Serum Glutamic -Pyruvic Transaminase (SGPT) level was raised in 75% of the positive cases as compared to the 25% of the seronegative patients. The seropositive cases had a comparatively higher blood sugar level. Conclusion: HCV infection occurs more often in type II diabetics and further investigations should be done in diabetic patients with raised SGPT for the presence of chronic HCV infection. Keywords : Hepatitis C virus, Diabetes mellitus.